Design and implementation of high-speed digital system - Zhang, Junwu (2009)
This report focuses on the development of a high speed digital system for Signal Integrity and EMC analysis. The development of a high speed digital system consists of hardware design and VHDL coding to implement combination and sequential logics onto the system. Various high-speed digital circuit design techniques such as multi-layer board designs, impedance control, signal lines terminations and power-ground noise de-coupling were explored after the system is assembled. The radiated emissions profile of he system developed was measured using a GTEM cell.